2005
DOI: 10.1259/dmfr/17102411
|View full text |Cite
|
Sign up to set email alerts
|

Superimposition of 3D cone-beam CT models of orthognathic surgery patients

Abstract: Objectives-To evaluate the registration of 3D models from cone-beam CT (CBCT) images taken before and after orthognathic surgery for the assessment of mandibular anatomy and position.Methods-CBCT scans were taken before and after orthognathic surgery for ten patients with various malocclusions undergoing maxillary surgery only. 3D models were constructed from the CBCT images utilizing semi-automatic segmentation and manual editing. The cranial base was used to register 3D models of pre-and post-surgery scans (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
240
1
27

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(269 citation statements)
references
References 25 publications
1
240
1
27
Order By: Relevance
“…Pre-and posttreatment images were registered on the anterior cranial base surface on all studies, 3,7,12,16,21,25 and one was also superimposed on the left zygomatic arch. 12 …”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Pre-and posttreatment images were registered on the anterior cranial base surface on all studies, 3,7,12,16,21,25 and one was also superimposed on the left zygomatic arch. 12 …”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Regional superimposition in the cranial base does not completely define the movement of the mandible relative to the maxilla 9,10,[20][21][22][23] . Previous studies 20,22,[24][25][26] revealed that relative displacement of mandibular and maxillary skeletal and dental components is critical because the resulting information may differ from conclusions formulated from the cranial base superimposition.…”
Section: Discussionmentioning
confidence: 99%
“…ia.unc.edu/dev/download/imagine/index.htm). 9 The software compares both images using the intensity of gray scale for each voxel of the region, so that the pre-surgical cranial base was used as reference for the superimposition of post-surgery models (Fig 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology was employed by Cevidanes et al (2005) who found that the superimposition of pre and post operative CBCT models of orthognathic surgery patients is a valid and reproducible technique, ideally suited to examining treatment outcomes.…”
Section: Registering 3d Imagesmentioning
confidence: 99%